The development of village-owned enterprises: Lessons learned from Ponggok Village - Andrian Dolfriandra Huruta; Eranus Yoga Kundhani; Chistopher Ramaoli Manurung (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The Tirta Mandiri village-owned enterprises or BUMDes is one of the best village-owned enterprises in Indonesia. It has made these village-owned enterprises a learning center for others in Indonesia. Currently, Tirta Mandiri village-owned enterprises have the role of creating new business fields in Ponggok Village (Polanharjo District, Klaten Regency). This study applied a qualitative method by conducting a case study. The primary data gathered through in-depth interviews with seven key informants and two supporting informants. The secondary data collected through the business management and planning documents of the Tirta Mandiri village-owned enterprises. Tirta Mandiri village-owned enterprises have been able to develop seven business units in the form of Limited Companies (Ltd.). Their presence can increase the output, income, and labor (multiplier effect) of the Ponggok villagers. It is proven by the presence of new businesses in the community. The development of the Tirta Mandiri village-owned enterprises is inseparable from the social capital of the community as a foundation for the development of the village-owned enterprises themselves. Furthermore, community participation actualized through investments, which are a sign of the public’s trust in the village-owned enterprises. Money is energy, and planning is the compass, and authority is the driver where the village takes part in realizing its autonomy. Learning from experience is one way to create sustainable village-owned enterprises.